THE COQUETTE’S PRISON: ROSALIE MURRAY AND THE FAILURE OF HIGH-SOCIETY MARRIAGE AS A PATH TO AUTONOMY - Syofyan, Donny (Jurnal Ceteris Paribus, 2026)
Research on women's agency in Victorian literature typically focuses on the marginalized figure of the governess. At the same time, the upper-class coquette—who appears to wield power—remains overlooked in critical readings as a victim of systemic oppression. This research examines the coquette’s prison in Anne Brontë’s Agnes Grey, specifically analyzing how Rosalie Murray’s pursuit of high-society marriage serves as a mechanism of self-erasure rather than a path to autonomy. The study employs a qualitative approach rooted in feminist literary criticism and historical realism. The data consist of textual evidence from the novel, analyzed through close reading and character-comparative analysis. The research evaluates the transition from pre-marital performative power to post-marital domestic entrapment. The results indicate that Rosalie’s flirtatious artillery provides only a temporary and illusory agency. Upon marrying Sir Thomas Ashby for rank and wealth, she experiences a catastrophic loss of freedom, becoming a prisoner and a slave within the physical and psychological enclosures of Ashby Park. The research concludes that Victorian high-society marriage, when divorced from moral compatibility, leads to psychological petrifaction. Further studies are recommended to employ a digital humanities approach to map motifs of spatial and psychological confinement across the broader canon of the Brontës and to identify systemic patterns of gender inequality.